Theoretical simulation of the optimal relation between active material, binder and conductive additive for lithium-ion battery cathodes - Miranda, Daniel (2019)
The cathode formulation for lithium-ion batteries has been optimized taking into consideration different active material, polymer binder and conductive additive ratios. Theoretical simulations have been carried out to evaluate the influence of different materials relative contents in the electrode performance, at various discharge rates. Simulations were performed by the finite element method applying the Doyle/Fuller/Newman model for two different active materials (C-LiFePO4 and LiMn2O4) and some results were compared with experimental data. The optimization of the electrode formulation is dependent on the maximum value of n, defined as the ratio polymer binder/conductive additive. The electrical conductivity of the cathode depends on the conductive material, thus it is dependent on the ratio n. The optimum balance of the cathode components is reported considering the performance and the mechanical stability.